Will be always be special? Extending humanity, shrinking uniqueness - Lumbreras Sancho, Sara (My University, 2016)
There is a vast array of characteristics that distinguish human beings from the rest of animals. We propose that these differential characteristics can be classified as: highly specific physiological traits (1), high-level social interactions (2), complex language (3), flexible behaviour, theory of mind and consciousness (4), development and use of technology (5), art (6) and spirituality (7). The first kind of differences could be understood as contingent upon the random avenues of evolution, even if some of these traits might have enabled the development of the others. It is the rest of them which seem a necessary part of human nature. In general, societies have a tendency to xenophobia (i.e. denying the humanness of the individuals outside the group). For instance, at some point, for western societies, African slaves or Native Americans were not considered human, with claims that they did not share the same intellectual abilities or spiritual nature of their European counterparts. The definition of humanity was then extended progressively to include more members, fulfilling the moral obligation to give human dignity to all beings that deserve it. At the same time, some features that were considered uniquely human had to be dropped from this list. For instance, even though at some point only humans were considered able to recognise themselves in a mirror, it was shown that some other primates, cetaceans and corvids can do it as well. In addition, tasks that apparently only a human could tackle have now been solved by machines (with Deep Blue beating Kasparov at chess being one of the most relevant examples). This has the effect of shrinking the list of uniquely human abilities. The latest example is particularly interesting from the point of view of some transhumanists such as Ray Kurzweil, for whom machines will be eventually display all the characteristics that are currently considered specifically human, including spirituality, but without being subject to our physical limitations. However, Kurzweil’s spiritual machines do not share our biological substrate. Even if a complete simulation of the human features above was possible it would be problematic to recognize that these machines are indeed human. The essence of humanness is subjective: using a language does not necessarily mean understanding it (as in John Searle’s Chinese room experiment), just as showing signs of empathy does not necessarily mean having feelings of compassion. A functionalist view would however miss these differences. This paper reflects on the apparent trend of extending humanity and shrinking uniqueness and its moral implications, with a special emphasis on the issues brought by functionalism and the ideas of some transhumanists, particularly the ones that defend extensive humanisms.